Extraction of xanthone derivatives from mangosteen (Garcinia mangostana L.) pericarp with virgin coconut oil by supercritical carbon dioxide - Kok, Siew Lee (2022)
Mangosteen (Garcinia mangostana L.) pericarp (MP), a by-product from mangosteen products is known to be loaded with xanthone, a popular phenolic compound with various functional benefits such as antioxidant and antimicrobial. Hence, the purpose of this research was to investigate the separation of xanthone from mangosteen pericarp with virgin coconut oil (VCO) by supercritical carbon dioxide (scCO2). The research began with optimising the yield of mangosteen pericarp extract (MPE), xanthone concentration, xanthone recovery and total phenolic content (TPC) where scCO2 extraction were done under fixed CO2 mass flowrate (18 g/min) and dynamic extraction (420 min) by varying the pressure (230 to 430) bar, temperature (50 to 70) °C and concentration of VCO (20 to 40) % as co-extractant using Box-Behnken design. The extract obtained from optimised conditions was characterised for α-mangostin and γ-mangostin with ultra-performance liquid chromatography (UPLC). It was found that %VCO had the most profound positive impact on the MPE yield and TPC, while pressure was the most significant factor affecting xanthone recovery. The best conditions (430 bar, 70°C, 40% VCO) predicted by response surface methodology (RSM) produced MPE yield (31.0%), xanthone concentration (28.2 mg/g), recovery (20.9%), TPC (1,473 mg GAE/ 100 g MP), α-mangostin (32.2 mg/g), and γ-mangostin (7.2 mg/g). VCO was seen to promote the mass transfer of xanthone from solid matrix into VCO phase, and subsequently scCO2 phase as elucidated by Pardo-Castaño model I (PC-I). Following that, ANOVA and broken intact cell (BIC) model differentiated the overall extraction curve (OEC) into three zones based on the extraction rate and suggested 100 min as the most efficient extraction time. The extraction performances and the quality of MPEs were reproduced when the process with the best conditions was scaled up based on the similarity of solvent mass to feed mass ratio (S/F) at different scales factors (1.0, 1.6, and 2.2), indicating that simultaneous increase of targeted compound and extraction solvent; similar OEC and product could be obtained. Meanwhile, the partial carbon footprint (PCF) was determined with Soxhlet (2.41 kg CO2 e/ g xanthone) being the most CF efficient in xanthone extraction process followed by maximised scCO2 (scale 1.6, 120 min extraction) process (3.43 kg CO2 e/ g xanthone). Therefore, it is suggested that scCO2 extraction with VCO could be used in extracting bioactive compounds from other plant matrices.